Improving Students' Critical Thinking and Self-Efficacy by Learning Higher Order Thinking Skills Through Problem Based Learning Models - Saepuloh, Dadang; Sabur, Ambuy; Lestari, Sri; Mukhlishoh, Siti U’tiyatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Higher-order thinking skills critical to being applied and developed in learning. Because the learning activity is focused on the higher-order thinking skills development, then learning activities will be more influential, effective, and efficient, so that the intellectual abilities of teachers and students become more skilled, it positively will affect the increase in the quality of education. There is a gap in students' critical thinking ability based on the pre-research survey results. The basic level of thinking is in the poor category, and self-efficacy is still lacking. This study aims to determine the extent to which the application of higher-order thinking skills learning through the problem-based learning (PBL) model improves student's critical thinking and self-efficacy. This study uses a quasi-experimental design and data collection techniques in tests, questionnaires, and observation sheets. This study's population was 123 students, sampling using a convenience sampling technique so that the sample used was 62 students. Based on the research results, there are differences. There is an increase between students' critical thinking skills and self-efficacy who use the PBL model rather than the conventional model. The research result implies that the PBL model is highly recommended for economics teachers. Still, it is necessary to provide innovation in the learning model so that in the learning process, it uses one model and innovates with other models.